Inverse Position Solution and Workspace Analysis of a Novel 3T2R Redundantly Actuated Hybrid Mechanism - Wang Shusen; Mei Ying; Li Ruiqin (Jixie chuandong)
A novel 3T2 R redundantly actuated hybrid mechanism is proposed. First,the motion principle of realizing the three- dimensional translational and two- dimensional rotation motion of this mechanism are analyzed by using the screw theory. The DOF of this mechanism is calculated,and the driving joints are chosen and discussed. Then,the inverse position solution equation is established by using analytical method. Next,based on the inverse position solution and combining with the constraints condition of this mechanism,its workspace is studied by using the numerical search method,and performance superiority of the mechanism is analyzed. At last,the inverse position solution equation is solved by using MATLAB and the results simulation verification is carried out by using ADAMS,and the correctness of the inverse position solution model and the realizability of the mechanism are verified.